Improved Productivity of NAD+ Reduction under Forced Convection in Aerated Solutions. Issue 5 (30th November 2021) - Le, Thi Xuan Huong; Gajdar, Julius; Vilà, Neus; Celzard, Alain; Fierro, Vanessa; Walcarius, Alain; Lapicque, François; Etienne, Mathieu
Abstract: The regeneration of the NADH cofactor is crucial for bioelectrocatalytic reactors. This can be achieved by using an electrochemical mediator such as the rhodium complex [Cp*Rh(bpy)Cl] +, but the overall reduction process suffers from the interference of molecular oxygen. This interference can be avoided by using a second porous working electrode (acting as a real oxygen filter) positioned near the surface of the first working electrode. To fabricate the oxygen filter, platinum particles were deposited on the surface of a carbon paper. NADH could be produced in the presence of the oxygen filter with a faradaic yield at 63.4 %, very close to the yields obtained without the filter at 61.7 % in a fully N2 ‐degased medium, and only at 10.6 % in the presence of oxygen. Moreover, the productivity was also increased by nearly a factor of four. Therefore, the proposed concept of the oxygen filter offers a new avenue in the current strategies for NADH regeneration in biocatalytic reactors based on electrochemical methods. Abstract : Applying a filter : The interference of oxygen on electrochemical regeneration of NADH in aerated solutions is removed by using an electrochemical oxygen filter, prepared through the deposition of Pt nanoparticles on carbon paper. The filter successfully removes oxygen molecules in the vicinity of the working electrode under convective conditions.